IMPLEMENTASI PENANGGULANGAN PENYEBARAN COVID-19 DI TEMPAT WISATA AIR TERJUN MANGKOL - M. Iqbal Arrosyad; Nurjannah (Bajang Institute, 2021)
The implementation of preventing the spread of COVID-19 at Mangkol Waterfall tourist attractions is carried out as a form of service at the time of the corona pandemic to help to break the chain of spreading the virus in tourist attractions. The results of preliminary observations found that the problem was that medical protocols had not been implemented such as recommendations for the use of masks for visitors, had not carried out body temperature checks, and were not equipped with handwashing infrastructure. visitors. This service aims to implement health protocols during the spread of Covid 19 to prevent transmission of the virus to visitors and break the chain of virus spread. The service method is carried out through the initial observation stage or situation analysis, the service planning stage, the service implementation stage, and the evaluation. The results of this service are the planning stage based on the observation that there is no application of health protocols at tourist sites, the implementation stage through training and provision of health protocol facilities, and the evaluation stage by implementing or implementing health protocol signs. for visitors and tourism managers of Mangkol Waterfall.